Engineering Undergraduates’ Self-Assessment in Delivering Technical Oral Presentations in ESL Context - Abdelmadjid, Benraghda; Noor Raha, Mohd Radzuan (American Scientific Publisher, 2018)
In recent years, alternative assessments have progressively gained attention in L2 speaking. An area which has received significant attention in the ESL literature has been the implementation of self-assessment strategy. The purpose of the present study is to find undergraduates’ perceptions pertaining to the use of self-assessment on technical oral presentations. In order to achieve this aim, the study conducted 113 engineering undergraduates from the Faculty of Civil Engineering and Earth Resources to be involved in this research. The study delved into the participants’ perceptions on self-assessment in delivering technical oral presentations. A questionnaire which had been adapted from previous studies was found to be reliable and was distributed to the participants. The results of the study revealed that the engineering undergraduates’ perceptions on self-assessment were positive. According to the findings of the study, it can be concluded that implementing self-assessment technique among Malaysian undergraduates can be helpful in overcoming some of their oral presentation difficulties. Hence, the results of the study have clear implications on teaching and learning. Educators can implement self-assessment technique as an autonomous learning opportunity to alleviate their students’ oral presentation apprehension. The strategy can polish the oral presentation skills of individuals in both academic and professional spheres.